RAN Tests Based on Inhibitory Control: A Study on its Concurrent and Predictive Validity - Sellés Nohales, María Pilar; Martínez Giménez, Tomás (Revista de Investigación en Logopedia, 2025)
Although Rapid Automatized Naming (RAN) has been repeatedly shown to be related to reading access and development, the nature of this link has not yet been clearly established. Currently, executive functions, especially inhibitory control, are considered as one of the possible explanatory factors of this relationship. This has led to the emergence of new RAN proposals, with a greater demand for inhibitory control during execution. However, there are still few studies that have used this type of RAN, especially in pre-reading students, and data on the validity of these new tests are lacking. To analyze the concurrent and predictive validity of this test, a longitudinal study was conducted involving 82 4-year-old girls and boys. At time 1, they completed two RAN tests: one that demanded greater inhibitory control and a traditional (non-alphanumeric) one. At time 2, two years later, the same group of students were assessed on different reading measures. The results show that the RAN Inhibition has a good predictive validity for reading, especially in word decoding. It is superior in several aspects to traditional RAN tests, with which, however, it has shown a moderate concurrent validity. This also seems to support the hypothesis that inhibitory control could be a new explanatory factor in the relationship between RAN and reading.